Statistical Machine Translation - Hassan Awadalla, Hany; Darwish, Kareem (Natural Language Processing of Semitic Languages, 2014)
We introduce a brief introduction to statistical machine translation for semitic languages along with an overview of machine translation approaches. We discuss the special consideration that should be taken into account when developing SMT systems for Semitic languages. We discuss segmentation techniques for Semitic SMT; and finally we introduce a detailed guide on how to build an SMT using freely available resources.